2018
DOI: 10.13189/ujer.2018.060305
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Positive Thinking Skills, Academic Locus of Control and Grit in Adolescents

Abstract: The main purpose of this study is to examine the possible relationships between academic locus of control, positive thinking skills and grit in high school students. The participants of the research are composed of 288 adolescents continuing their high school education from 4 different schools in Ağrı, Turkey which were selected with convenient sampling. 168 of the participants are male and 120 are female students. Pearson's moment correlation analysis was used for determining relations among variables, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
2
14
1
4
Order By: Relevance
“…<0.05. These results contradict the study of Çelik and Sarıçam (2018) which suggests that internal academic locus of control and positive thinking skills are important predictors of grit, though it only explained 50% of the grit's total variance. One possible reason is that although individuals with high levels of self-control can regulate their actions (e.g.…”
Section: Grit Internal Locus Of Controlcontrasting
confidence: 94%
See 1 more Smart Citation
“…<0.05. These results contradict the study of Çelik and Sarıçam (2018) which suggests that internal academic locus of control and positive thinking skills are important predictors of grit, though it only explained 50% of the grit's total variance. One possible reason is that although individuals with high levels of self-control can regulate their actions (e.g.…”
Section: Grit Internal Locus Of Controlcontrasting
confidence: 94%
“…One possible explanation for this is that although an association may seem present between the two variables, it is still possible that there are still other important facets or factors that might have an impact on the independent variable. This can be supported in a study by Çelik and Sarıçam (2018) which demonstrated that directly investigating the relationship between internal locus of control and grit remains scarce. This only implies that although some individuals believe that they are in control over the events that influence their lives, it does not necessarily mean that they can persist in achieving long-term goals.…”
Section: Grit Internal Locus Of Controlmentioning
confidence: 79%
“…De hecho, en las instituciones educativas, la medición más utilizada del desempeño en relación con el grit es el promedio académico (Lam & Zhou, 2019). No obstante, la literatura ha empezado a sugerir nuevas formas para evaluar el desempeño académico en relación con esta variable, como lo son las autopercepciones hacia el rendimiento académico (Buzzetto-Hollywod et al, 2019;Celik & Sarıçam, 2015;Usher et al, 2019), la motivación escolar (Eskreis-Winkler et al, 2014; Guzmán-Zamora & Gutiérrez-Garcia, 2020) y las estrategias para el aprendizaje (Córdova, 2021;Sáez-Delgado et al, 2021;Weisskirch, 2018).…”
Section: Estudio 2: Validez De Criteriounclassified
“…Faktor internal diantaranya adalah hope (A. Duckworth, 2016), motivasi belajar (Zhao et al, 2017, growth mindset (Zhao et al, 2017), motivasi (Reraki et al, 2015), academic locus of control (Çelik & Sariçam, 2018). Sedangkan factor eksternal adalah parenting style (Dunn, 2017), a culture of grit (Çelik & Sariçam, 2018), dan the playing fields of grit (Çelik & Sariçam, 2018).…”
Section: Pendahuluanmentioning
confidence: 99%